Considering the Brazilian regional relations in the behavioral clinic - Silva, Jandilson Avelino da (Perspectivas em Análise do Comportamento, 2023)
Regional relations in Brazil are unbalanced, are reflected in social interactions and identity constructions and, therefore, need to be considered within psychotherapeutic processes. Although some sociocultural themes have been included in the discussion of these clinical practices, the clients’ place of origin has been little considered. Therefore, understanding the continental size of Brazil, the enormous cultural differences between its different regions and the historically established relations of power between them, this theoretical study intends, through a narrative review of the literature, to discuss the need for the regionalization of the behavioral clinical practice of the country. In this sense, regionalizing means emphasizing regional cultural aspects, including minority identities resulting from interactions between regions. The unequal relations between the Northeast and the other regions of the country will be taken as a reference, as a way of elucidating this proposal. Therefore, it is proposed that the relationships between the clinical-social psychological perspective of Green FAP, the concept of intersectionality, and the ADDRESSING evaluative model, together, can help in this process of regionalization of psychological issues in the clinical process.